Influence of Sowing Dates and Sowing Methods on Growth and Seed Yield of Black Cumin (Nigella sativa L.) - Waliullah, Md.; Mokter Hossain, Md.; Habibur Rahman, Md. (Department of Agronomy and Horticulture, IPB University, 2021)
Nigella sativa L. is widely used medicinal plant throughout the world. In Bangladesh it is mainly used as spices in preparing various food items. Sowing time and sowing methods are the influential factors to produce higher seed yield of black cumin. Therefore, this study was undertaken to find out a suitable sowing date and method to produce higher seed yield of black cumin. The two-factor experiment comprised with four sowing dates (1st November, 15th November, 1st December and 15th December) and two sowing methods (line sowing and broadcast seeding). The experiment was carried out following randomized complete block design with three replicates. Results showed that plant growth, yield contributing traits and yield of black cumin significantly influenced by sowing dates and methods. It was observed that the line sowing method compared to broadcast seeding and 1st December sowing among the other sowing dates exhibited higher plant growth with greater production of seed. The combine effect of sowing time and sowing methods showed significantly influenced on black cumin seed production. It was observed that the 1st December sowing with line sowing method increased the seed yield as compared to other sowing dates and methods. From the findings of this study it can be concluded that 1st December following line sowing method would maximize plant growth, yield contributing traits and seed yield of black cumin in Bangladesh.